The Effect of Price and Product Quality on Consumer Satisfaction Levels : Case Study On Consumers At Terracotta Cafe Lamongan - Puguh Cahyono; Deajeng Octavianti Masfufah (Research Trend in Technology and Management, 2024)
From the economic aspect, the development of cafes has a positive impact on the development and business activities of the creative economy. The fierce competition demands that entrepreneurs must be ready and able to compete. Terracotta Cafe is a hangout place that is currently crowded with young people, especially those in Lamongan. The purpose of this study is to find out the factors that affect the level of consumer satisfaction. This study uses a quantitative approach. The consumer population at Terakota Cafe is 21,975 people and the sample needed is based on the calculation of the slovin formula of 100 respondents. Data were collected using questionnaires. Data processing using SPSS with Multiple Linear Regression Analysis technique. The results of the study show that partially and simultaneously the price and quality of products affect consumer satisfaction. The dominant variable of influence is product quality.